(untitled) (Global Journal of Science Frontier Research, 2011)
This study assessed the flora species composition and range condition of Jibiro grazing reserve in Song Local Government Area of Adamawa State, Nigeria. Range factors used for the assessment include botanical composition of herbaceous vegetation, ground cover, litter cover, plant vigour, erosion level, and trees/shrubs density on range sites. Plant health (vigour) was rated as stunted, erosion was slight, the mean tree/shrub density per hectare was 475 trees/shrubs and litter cover was 27%. The relative density of the herbaceous species shows that Aristida longiflora had the highest with 24.66% (1953 species) while Cacia obtusifella has the lowest of 0.89% (71 species). The overall results were scored on the range condition score card; giving a total score of 45%. This was then compared to a key for rating condition, which puts the range in a fair condition. Range management and improvement practices such as prescribed burning, range seeding and reseeding, control of rate of grazing and other sustainable management practices that will range trend and improvement within the reserve were recommended.